2021
DOI: 10.7717/peerj-cs.533
|View full text |Cite
|
Sign up to set email alerts
|

AndroAnalyzer: android malicious software detection based on deep learning

Abstract: Background Technological developments have a significant effect on the development of smart devices. The use of smart devices has become widespread due to their extensive capabilities. The Android operating system is preferred in smart devices due to its open-source structure. This is the reason for its being the target of malware. The advancements in Android malware hiding and detection avoidance methods have overridden traditional malware detection methods. Methods In this study, a model employing AndroAna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
12
0
3
Order By: Relevance
“…is method involves disassembly of source code and analyzing it to check the presence of malware without executing the source code and depend only on malware abstraction characteristics and application byte code. Mostly, reengineering is applied [41][42][43].…”
Section: Static Dynamicmentioning
confidence: 99%
See 2 more Smart Citations
“…is method involves disassembly of source code and analyzing it to check the presence of malware without executing the source code and depend only on malware abstraction characteristics and application byte code. Mostly, reengineering is applied [41][42][43].…”
Section: Static Dynamicmentioning
confidence: 99%
“…Collects temporal instructions. Applications are in format APK or archive in a zip package [41][42][43].…”
Section: Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…At last, the URL is classified and detected by SoftMax function with global feature. In the study conducted earlier [16], an algorithm was suggested which employs AndroAnalyzer, a model that applies both deep learning systems and static analysis. In this study, the analysis was conducted on original datasets comprising 7,622 applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of groups and categories of Android malware APKs, such as worms, botnet, rootkits, ransomware, and Trojans [ 3 ]. These Android malware attacks can exploit metamorphic and polymorphic procedures to obfuscate traditional malware recognition and detection algorithms.…”
Section: Introductionmentioning
confidence: 99%